Barriers toward the practice of healthy behaviors among patients with non-communicable diseases in Gaza Strip, Palestine. (June 2021) - Albelbeisi, Ahmed Hassan; Albelbeisi, Ali; El Bilbeisi, Abdel Hamid; Taleb, Mahmoud; Takian, Amirhossein; Akbari-Sari, Ali
Objectives: Non-communicable diseases are non-infectious health conditions caused by genetic, physiological, environmental, and behavioral factors. Currently, non-communicable diseases account for almost two-thirds of deaths globally. This study aimed to explore the patients' adherence level to the key recommendations, and the main barriers toward the practice of healthy behaviors among non-communicable diseases patients. Method: This cross-sectional study was conducted among a representative sample of non-communicable diseases patients, receiving care in five primary healthcare centers in the Gaza Strip, Palestine. An interview-based questionnaire about demographics, medical history, and barriers toward the practice of healthy behaviors was developed and collected based on the health belief model and the theory of planned behaviors. Independent samples t -test, one-way analysis of variance, chi-square, and Fisher's exact test were used for analysis. Results: Four hundred patients with non-communicable diseases, aged (53.06 ± 10.03) years old, (56.8% females and 43.3% males) were included in this study. The patient's adherence was reported as 50.1%, standard deviation = 18.3 in terms of attended regular physical activity, and 44.0%, standard deviation = 15.4 in terms of eating a healthy diet. The main barriers to being active among patients were lack of accessibility to materials, lack of social support, and lack of reminder; while in terms of eating a healthy diet were lack of accessibility to materials, lack of social support, and lack of self-efficacy. Conclusion: The non-communicable diseases patients' adherence to healthy behaviors is suboptimal. Varied implementation strategies targeting the main barriers are extremely required to enhance the access to physical activity infrastructure, affordable healthy diet options, and to reinforce the change toward healthy behaviors at all levels.